ESTRAK IKAN GABUS (CHANNA STRIATA ) UNTUK MENINGKATKAN KADAR HEMOGLOBIN PADA IBU NIFAS ANEMIA DI RSUD Hj.ANNA LASMANAH BANJARNEGARA - admjurnalsiji polibara; Umi Nur Fajri; Suharyo Hadisaputro; Ariawan Soejoenoes (Jurnal Ilmiah Medsains, 2020)
In labor with CS, the mortality rate is twice the rate of vaginal deliveries. SC action can result in changes in the physiological functions of the body, including loss of a lot of blood during surgery which can cause anemia. The research objective was the effect of snakehead fish extract (Channa Striata) on the increase in hemoglobin levels in anemic postpartum mothers. Snakehead fish has the highest albumin content compared to other fish. Albumin has the function of accelerating the recovery of divided / damaged body cell tissues and also as a means of carrying materials that are less water-soluble through blood plasma and cell fluids, one of these materials is iron.This type of research is quasy experimental with pre test post test control group design. Sample of 30 respondents. The intervention group was given snakehead fish extract, antibiotics and Fe tablets for the control group was given antibiotics and Fe tablets. The independent variable was snakehead fish extract and the dependent variable was hemoglobin level. The research instrument of snakehead fish extract using observation sheets, for Hb levels using a spectrophotometer. Data analysis using Independent t test. Research result; 1000 mg of snakehead fish extract for 14 days increased the average hemoglobin level by 1.08 g%. Suggestion: postpartum mothers who have anemia in addition to drinking Fe tablets also drink snakehead fish extract. Keyword : Snakehead Fish Extract, Hemoglobin Level, Anemia, Post Post SC